Blockchain with Hyperledger Fabric : Build decentralized applications using Hyperledger Fabric 2, 2nd Edition /: Build decentralized applications using Hyperledger Fabric 2, 2nd Edition. (2020) - Gaur, Nitin; O'Dowd, Anthony; Novotný, Petr; Desrosiers, Luc; Ramakrishna, Venkatraman; Baset, Salman A
No abstract available